Community Service Regarding Good and Right Hands Washing in Elementary School 25 City of Bima - Suryati; Nur Islamiyati (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service through health education for children regarding proper and correct hand washing is one of the sanitation measures by cleaning hands and fingers using water and soap to keep them clean and break the chain of germs. The role of parents is crucial in providing information every day as a reminder that the Puskesmas and Health Workers have provided Health Education through visits to schools in the Santi City of Bima, Increasing knowledge related to proper and correct handwashing steps for children to prevent disease by providing counseling in every elementary school in Bima City in collaboration with health and government agencies. Based on the preliminary survey, many Elementary School 25 City of Bima students still need to wash their hands before and after eating. The aim is to provide counseling regarding proper and correct handwashing steps for children so that Indonesia is free from disease. The activity method is carried out by making pre and post-test questions that measure the level of knowledge before and after being given counseling. Based on the results of the assessment before (pretest), counseling was provided. Namely, 56 children with less knowledge (85%) had sufficient knowledge of 10 people (15%). Experienced an increase after counseling was carried out by conducting a reassessment (post-test) where children who had less knowledge, namely five people (7%), nine people (14%) were good, and 52 people (79%) were good.